Biological factors contributing to bark and ambrosia beetle species diversification. (1st May 2017) - Gohli, Jostein; Kirkendall, Lawrence R.; Smith, Sarah M.; Cognato, Anthony I.; Hulcr, Jiri; Jordal, Bjarte H.
Abstract: The study of species diversification can identify the processes that shape patterns of species richness across the tree of life. Here, we perform comparative analyses of species diversification using a large dataset of bark beetles. Three examined covariates—permanent inbreeding (sibling mating), fungus farming, and major host type—represent a range of factors that may be important for speciation. We studied the association of these covariates with species diversification while controlling for evolutionary lag on adaptation. All three covariates were significantly associated with diversification, but fungus farming showed conflicting patterns between different analyses. Genera that exhibited interspecific variation in host type had higher rates of species diversification, which may suggest that host switching is a driver of species diversification or that certain host types or forest compositions facilitate colonization and thus allopatric speciation. Because permanent inbreeding is thought to facilitate dispersal, the positive association between permanent inbreeding and diversification rates suggests that dispersal ability may contribute to species richness. Bark beetles are ecologically unique; however, our results indicate that their impressive species diversity is largely driven by mechanisms shown to be important for many organism groups.